Neurophysiological differential diagnostic markers in hereditary neuropathy with liability to pressure palsies and chronic inflammatory demyelinating polyradiculoneuropathy - D. A. Grishina; N. A. Suponeva (Нервно-мышечные болезни, 2023)
Background. Today, the issues of differential diagnosis of chronic hereditary and acquired demyelinating neuropathies are still relevant. The variety of phenotypic variants of chronic inflammatory demyelinating polyradiculoneuropathy and hereditary neuropathy with liability to pressure palsies, their remitting course and the non-specificity of neurophysiological changes necessitate the identification of clear markers that can help in the differential diagnosis of the neuropathies under discussion already at the stage of the analysis of the electroneuromyographic study data.Aim. To determine neurophysiological differential diagnostic markers in the manifestation of chronic inflammatory demyelinating polyradiculoneuropathy and hereditary neuropathy with liability to pressure palsies.Materials and methods. A retrospective analysis of the data of neurophysiological examination of 25 patients with hereditary neuropathy with liability to pressure palsies and 25 patients with chronic inflammatory demyelinating polyradiculoneuropathy.Results. A combination of such indicators as the age of the onset of the disease <33 years, the latency of the dM-wave with m.ADM ><3.7 ms and with m.AH ><4.8 ms (AUROC >0.7), the value of the conduction velocity along of the motor fibers of the ulnar nerve at the level of the elbow joint <37.5 m/s (AUROC >0.8), the conduction velocity along of the sensory fibers of the median nerve at the level of the wrist <48 m/s (AUROC >0.8), absence of conduction block along the median nerve in any area, and also the presence along the ulnar nerve at the level of the elbow joint is characteristic of hereditary neuropathy with liability to pressure palsies and allows to exclude chronic inflammatory demyelinating polyradiculoneuropathy.Conclusion. Neurophysiological markers have been identified that can help in the differential diagnosis of two chronic remitting demyelinating neuropathies: chronic inflammatory demyelinating polyradiculoneuropathy and hereditary neuropathy with liability to pressure palsies. However, only a combined analysis of clinical, anamnestic and paraclinical data makes it possible to establish a final diagnosis.